Control of cleavage cycles in Drosophila embryos by fruhstart. - Großhans, J.; Muller, H.A.; Wieschaus, E. (Developmental Cell, 2003)
Early metazoan development consists of cleavage stages characterized by rapid cell cycles that successively divide the fertilized egg. The cell cycle oscillator pauses when the ratio of DNA and cytoplasm (N/C) reaches a threshold characteristic for the species. This pause requires maternal factors as well as zygotic expression of as yet unknown genes. Here we isolate the zygotic gene frühstart of Drosophila and show that it is involved in pausing the cleavage cell cycle. frs is expressed immediately after the last cleavage division. It plays a role in generating a uniform pause and it can inhibit cleavage divisions when precociously expressed. Furthermore, the expression of frs is delayed in haploid embryos and requires activity of the maternal checkpoint gene grapes. We propose that zygotic frs expression is involved in linking the N/C and the pause of cleavage cycle.